2015
DOI: 10.1371/journal.pone.0130833
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Diffusion Tensor Imaging: Assessment of Axon and Myelin Sheath Integrity

Abstract: PurposeTo investigate the potential of diffusion tensor imaging (DTI) parameters as in-vivo biomarkers of axon and myelin sheath integrity of the median nerve in the carpal tunnel as validated by correlation with electrophysiology.MethodsMRI examinations at 3T including DTI were conducted on wrists in 30 healthy subjects. After manual segmentation of the median nerve quantitative analysis of fractional anisotropy (FA) as well as axial, radial and mean diffusivity (AD, RD, and MD) was carried out. Pairwise Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 55 publications
6
108
1
Order By: Relevance
“…To a lesser extent, a decrease in RD and AD has been reported in CTS . One CTS study correlated AD with compound muscle action potential (CMAP), which is inferred to be indicative of axon integrity, while RD and FA correlated with sensory nerve conduction velocity (sNCV), which reflects myelin sheath integrity. Cubital tunnel syndrome of the ulnar nerve has been found to decrease FA; moreover, fiber discontinuities indicating severe nerve damage were detected with DTT …”
Section: Peripheral Nerve Dti Applicationsmentioning
confidence: 99%
“…To a lesser extent, a decrease in RD and AD has been reported in CTS . One CTS study correlated AD with compound muscle action potential (CMAP), which is inferred to be indicative of axon integrity, while RD and FA correlated with sensory nerve conduction velocity (sNCV), which reflects myelin sheath integrity. Cubital tunnel syndrome of the ulnar nerve has been found to decrease FA; moreover, fiber discontinuities indicating severe nerve damage were detected with DTT …”
Section: Peripheral Nerve Dti Applicationsmentioning
confidence: 99%
“…Mashayekh et al reported on 106 patients undergoing 146 scalene injections using CT guidance. In all cases, needle tip localization was satisfactory [42]. No major complications occurred, although 11% reported minor complications such as needle site pain, temporary brachial plexus block, undesired muscle weakness, dysphagia and Horner sign.…”
Section: Interventional Imagingmentioning
confidence: 79%
“…Nerve conduction studies Needle electromyography [5,34] Local anaesthetic injection test [5,[35][36][37][38] -MR neurography [39,40] Diffusion tensor imaging [41][42][43][44][45] Brachial plexus ultrasound [46,47] When it comes to supporting the suspected diagnosis, the mainstays of tests in ATOS are duplex ultrasound, arteriography, haemodynamic testing (e.g., finger plethysmography) at rest, and, with provocative manoeuvres, CT angiography and MR angiography [5]. Invasive arteriography and angiography are for detecting complications of ATOS such as thrombosis, embolisation, and aneurysm.…”
Section: Ntosmentioning
confidence: 99%
“…Interest is growing in the use of DTI tractography in the assessment of CTS as a result of evidence for its diagnostic value. A correlation between median DTI metrics and electrophysiology for the carpal tunnel nerve has been reported, suggesting a role for DTI in the in vivo assessment of axon and myelin sheath integrity 7,[42][43][44] . According to a meta-analysis published in 2016 that included 316 patients and 293 healthy controls across 12 studies, fractional anisotropy of the median nerve was significantly lower in patients with CTS, and this measure enabled diagnosis of CTS with an overall sensitivity of 82.8% and a specificity of 77.8% 44 .…”
Section: Entrapment Neuropathiesmentioning
confidence: 95%